WebGL HOTSHOT - Williams, Mitch (Packt Publishing, 2014)
Create interactive 3D content for web pages and mobile devices In Detail This book presents many popular applications for the Web including examples of deploying 3D applications such as building interactive products for e-commerce, extending social media, visualizing big data, and more. It helps you master how to instantly create and deploy Web3D content, demonstrating a variety of common and unique web applications and exploring the artistic features of 3D. It is ideal for current web developers or those looking for a starting point to learn about 3D graphics technology in a bleeding-edge field. What You Will Learn Get well-versed with fundamental technologies of 3D graphics including the design of 3D objects, lighting scenes, and viewing scenes from various camera positions Discover how to send data to control 3D from a web browser to the graphics card for rich and engaging graphical presentation Understand the role of graphics card programming using shader languages to control the appearance of a 3D scene down to each individual pixel Explore how to load 3D objects created by artists in modeling tools in the background Integrate Web3D content with databases and other web applications such as social media to extend common applications with 3D Control the parameters of cameras such as field-of-view, removal of distant objects, and environmental effects such as fog and night scenes